Virulence and Antimicrobial Resistance Patterns of Salmonella spp. Recovered From Migratory and Captive Wild Birds - Ruhena Begum; Nilima Akther Asha; Diponkar Chandra Chanda Dipu; Milton Roy; Asikur Rahman; Md. Shahidur Rahman Chowdhury; Hemayet Hossain; Md. Rafiqul Islam; Md Bashir Uddin; Md. Mahfujur Rahman; Md. Mukter Hossain (Veterinary Medicine and Science)
ABSTRACT Background Salmonella spp., especially those are resistant to extended‐spectrum β‐lactamase (ESBL), are considered as major concern to global health due to their emergence and dissemination. Aim The aim of this study was to investigate the virulence and antimicrobial resistance (AMR) profile of Salmonella spp. from migratory and captive wild birds. Method A total 262 faecal samples were collected, and the identification of Salmonella spp. was carried out using a standard culture and PCR as well as molecular detection of virulence and AMR genes. Results The overall prevalence of Salmonella was determined to be 30.92% (95% CI = 25.63–36.75). Migratory birds exhibited highest prevalence (38.10%), whereas wild birds in captivity showed a lower prevalence (23.40%). The agfA gene was detected at a higher rate at 24.69%. Salmonella spp. exhibited 100% resistance to tetracycline, followed by 58% ampicillin and 46% streptomycin. In addition, there was a resistance rate to ceftriaxone of 17% and to colistin sulphate of 25%. Interestingly, levofloxacin alone displayed 100% sensitivity across all isolates, while ciprofloxacin and azithromycin showed 73% and 64% sensitivity, respectively. The MAR index was 0.25 and 0.42, and 74.07% of all isolates showed multidrug resistance (MDR). It was shown that migratory and captive wild birds contained ESBL genes blaTEM (94.34% and 49.06%) and blaSHV (13.33% and 10%), respectively. Genes responsible for sulphonamide (sul1) resistance were detected in 13.33% and 79% of wild and migratory birds, respectively. Conclusion Salmonella has been found in captive wild and migratory birds and could act as reservoirs for the transmission of MDR and ESBL bacteria.